Environmental impact assessment of alternative technologies for production of biofuels from spent coffee grounds - Wilberforce Kisiga; Manimagalay Chetty; Sudesh Rathilal (Energy Science & Engineering)
Abstract In the strategy to combat climate change that has been caused by the world's overdependence on fossil fuels, current research is focusing on the decarbonisation of the energy sector through the production of renewable cleaner energy, such as biofuels. Spent coffee grounds (SCGs), the waste stream of the coffee brewing industry, are a potential feedstock for the production of valuable products, including biofuels. However, the environmental implications for the valorisation of this valuable waste need to be investigated. This study assesses the environmental impacts of six biomass‐to‐fuel processing technologies using SCGs as a feedstock, with the aim of identifying the most environmentally friendly technology. A cradle‐to‐gate life‐cycle assessment (LCA) was conducted on fast pyrolysis, fermentation, anaerobic digestion (AD), hydrothermal liquefaction (HTL), gasification, and biodiesel production. The mass and energy balances obtained from Aspen Plus simulations served as the life‐cycle inventory data. Using the ReCiPe 2016 midpoint (H) and Eco‐Indicator 99 as the assessment methods, potential environmental impacts were calculated in OpenLCA software. Electricity generation and carbon dioxide emissions were the biggest contributors of environmental impacts. For each category, the maximum result was set to 100% and the results of the other variants were displayed in relation to this result. AD, with the smallest total weighted score (160), was the most environmentally friendly biomass‐to‐fuel processing route, while HTL, with the biggest total weighted score (893), was the worst. A sensitivity analysis indicated that the environmental performance of biofuel production from SCGs was highly influenced by energy input flows and the source of energy generation.